Nanostructured superhydrophobic silk fabric fabricated using the ion beam method - Oh, Ji-Hyun; Ko, Tae-Jun; Moon, Myoung-Woon; Park, Chung Hee (ROYAL SOC CHEMISTRY, 2014)
Superhydrophobic silk fabric surfaces with high-aspect-ratio nanostructures were fabricated using ion beam treatment. The ion beam irradiated silk fabrics were characterized for wettability, as well as other physical properties unique to silk. The nanostructures were produced in various configurations, ranging from columnar to hairy shapes, on the silk fibers through anisotropic etching using oxygen ion beam treatment. Subsequent hydrophobic coating on the nanostructured, superhydrophobic silk fiber surfaces was achieved with an increase of the static contact angle from 0 degrees for the pristine hydrophilic silk fabric to 170 degrees for the superhydrophobic silk fabric and with a decrease of shedding angle by less than 5 degrees, which is sufficient roll-off a water droplet to the silk fabric surface. Because the ion beam-treated side of silk fabric becomes superhydrophobic, while the opposite side, or body contacting side, remains pristine or superhydrophilic, an extreme asymmetric wettability can be achieved in the silk fabric, which improves its breathability by improving moisture transmittance through the fabric from the body to the outer surface. The luster and color of silk fabric before and after ion beam irradiation were found to exhibit no significant degradation. The breaking load of the silk fabric after the ion beam treatment was assessed to be mechanically durable in comparison to that of the pristine fabric. Therefore, after introducing the superhydrophobic property via the ion beam treatment, the silk fabric maintained its primary advantages, as a result, the range of its applications can expand into breathable self-cleaning clothing textiles, such as neckties, blouses and dresses.
Keywords: SURFACE; HYDROPHOBICITY; TRANSPARENT; ENHANCEMENT; SILICA; FILMS